Development of Interactive Learning Multimedia to Improve 5-6 Year Old Children's Understanding of Body Parts - Putri, Sindi Anjali; Fadlilah, Azizah Nurul (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2023)
Using unattractive teaching media will make it difficult for children to understand the lessons. This research aims to produce interactive multimedia learning in body parts material that has been proven valid and practical for children aged 5-6 years. This type of research uses the Alessi & Trollip development model. The subject of this research is Interactive Multimedia Learning Material on Body Parts, which goes through the planning, design, and development stages. The objects of this research were Group B children of Robbani Indralaya Kindergarten. The research procedures carried out in this research went through four stages: planning, design, development, and evaluation. Meanwhile, the data collection techniques used in this research are walkthrough, observation, interviews, and documentation. The data analysis technique uses walkthrough data analysis and observation data analysis. This media has proven to be valid and practical. Based on research on developing interactive multimedia learning material on body parts for children aged 5-6 years. So, this media can be used by teachers or parents to teach body parts to children aged 5-6 years.